No Tension: JWST Galaxies at $z > 10$ Consistent with Cosmological Simulations - Joe McCaffrey; Samantha Hardin; John H. Wise; John A. Regan (The Open Journal of Astrophysics)
Recent observations by JWST have uncovered galaxies in the very early Universe via the JADES and CEERS surveys. These galaxies have been measured to have very high stellar masses with substantial star formation rates. There are concerns that these observations are in tension with the ΛCDM model of the Universe, as the stellar masses of the galaxies are relatively high for their respective redshifts. Recent studies have compared the JWST observations with large-scale cosmological simulations. While they were successful in reproducing the galaxies seen in JADES and CEERS, the mass and spatial resolution of these simulations were insufficient to fully capture the early assembly history of the simulated galaxies. In this study, we use results from the Renaissance simulations, which are a suite of high resolution simulations designed to model galaxy formation in the early Universe. We find that the most massive galaxies in Renaissance have stellar masses and star formation rates that are consistent with the observations from the JADES and CEERS surveys. The higher resolution afforded by Renaissance allows us to model the build-up of early galaxies from stellar masses as low as 10${\mathstrut}^4 M_⊙$ up to a maximum stellar mass of a few times 10${\mathstrut}^7 M_⊙$. Within this galaxy formation paradigm, and after extrapolating forward in time the stellar masses in Renaissance where required, we find excellent agreement with JADES and CEERS. We find no tension between the ΛCDM model and current JWST measurements. As JWST continues to explore the high redshift Universe, simulations, such as Renaissance, will continue to be crucial in understanding the formation history of early embryonic galaxies.